The Influence of Aqua Regia Usage in the Leaching and Extraction Process of Silica from Coal Fly Ash - Perwitasari, Perwitasari; Anggorowati, Heni; Ulfa, Uli; Shabrina, Husna Muizzati; Adhiatma, Agus (Program studi Teknik Kimia UNS, 2024)
Waste from coal-burning power stations and other sectors that rely on coal as a source of energy is one of the environmental issues. Fly ash obtained from burning coal causes pollution in the surrounding environment. Subsequently, a great deal of study was conducted on the application of flying ash coal. Among the techniques for making use of the flying ash of coal is the extraction of silica. This study carried out silica leaching using Aqua Regia (a combination of HCl and HNO₃) with various ratios of 1:1, 1:3, and 3:1. The leaching process was carried out at varying temperatures of 30, 45, 60, 75, and 90 °C, with a leaching time of 1 and 2 hours. Precipitates containing silica were analyzed for their levels using XRF. The results of the study show that the ratio HCl:HNO₃ 3:1 is able to extract more silica than other solvent ratios.Keywords:Silica, Fly Ash, Leaching, HCl, HNO₃